Antigen Presentation by MHC-Dressed Cells - Nakayama, Masafumi (Frontiers in Immunology, 2015)
Professional antigen-presenting cells (APCs) such as conventional dendritic cells (DCs) process protein antigens to MHC-bound peptides and then present the peptide–MHC complexes to T cells. In addition to this canonical antigen presentation pathway, recent studies have revealed that DCs and non-APCs can acquire MHC class I (MHCI) and/or MHC class II (MHCII) from neighboring cells through a process of cell–cell contact-dependent membrane transfer called trogocytosis. These MHC-dressed cells subsequently activate or regulate T cells via the preformed antigen peptide–MHC complexes without requiring any further processing. In addition to trogocytosis, intercellular transfer of MHCI and MHCII can be mediated by secretion of membrane vesicles such as exosomes from APCs, generating MHC-dressed cells. This review focuses on the physiological role of antigen presentation by MHCI- or MHCII-dressed cells, and also discusses differences and similarities between trogocytosis and exosome-mediated transfer of MHC.